THE DEBT MANAGEMENT PATTERNS OF EDUCATIONAL LOAN RECIPIENTS AMONG POLYTECHNIC STUDENTS IN KOTA KINABALU, SABAH: AN EMPIRICAL STUDY - Hainnur Aqma Rahim; Ngau Duo Seng; Dicky Wiwittan Toto Ngadiman; Nor Asmat Ismail (International Journal of Accounting, Finance and Business, 2020)
There has been an increase in the number of students registering in higher learninginstitutions, but there is a big gap between the number of graduates and the number ofscholarships provided. Following that, the cost of education at both public and private higherlearning institutes is on the increase day by day. Other than having to spend money on learningpurposes like academic materials, stationery and so on, students are also affected by theincreased price of necessities, like food and others. This is because, they only depend on thescholarship, loan or financial assistance given by their parents. With this in mind, this studyseeks to investigate students' habit when it comes to managing their educational loans. Basedon the random sampling method, 352 students from the Polytechnic in Kota Kinabalu, Sabah(PKK) comprising of Sabah Bumiputera (66.5%), Sarawak Bumiputera (3.5%), Malay (14.1%),Chinese (4.1%), Indian (1.2%) and others (10.6%) were selected. The study finds that althoughthe students have received their loans, they are still having the financial burden due to theparents' lack of financial stability. Thus, students must be equipped with financial managementknowledge so that any financial problems they face can be addressed.